PENGEMBANGAN PRODUK INFUSED WATER REMPAH SEBAGAI UPAYA MENCAPAI SDGs 3 (KEHIDUPAN SEHAT DAN SEJAHTERA) BAGI MASYARAKAT KELURAHAN CANDIRENGGO KECAMATAN SINGOSARI KABUPATEN MALANG - Armadhani, Rio; Azizah, Wafiq Failila; Cahyani, Tasya Septhia; Ismi, Zahira Fitria; Wulansari, Suryaning; Shaktiaji, Naufal Anugrah; Utama, Candra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This service research has a goal to develop Spice Infused Water products that have useful value and see the community's response to Spice Infused Water products. The background of this study was due to the existence of various health problems at the research location, and it was found that the people at the research location had a lack of motivation in implementing a healthy lifestyle due to time limitations and difficulties in managing a healthy diet. This research adapts the research and service method with the following steps: preparation, implementation, and evaluation. Spice infused water products have passed laboratory tests at the Faculty of Agricultural Technology, Universitas Brawijaya on August 12, 2024 to test the contents in spice infused water drinks and on August 20, 2024 to determine the benefits of spice infused water products. Some of the parameters tested include: 1) Total sugar, 2) Potassium, 3) Vitamin C, 4) Salt, 5) Magnesium, 6) Antioxidants, 7) Nutrition fact (Total Sugar, Protein, Total Carbohydrates, Ash, Water, and Calories). Based on the results of trials and interviews with the public, it can be concluded that the Infused Water Spice product has good content for health and gets a good response from the community.